Поэт и Русалка: [роман] / Александр Бушков - Бушков Александр Александрович (Мамонты, 2011)
Экземпляры: РБ (20210624) / Инвентарный номер: 61784 / Цена: 30.00 / Авт.знак: Б 94 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6